2020
DOI: 10.3390/su12239955
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Impacts of Parameters on Surrogate Safety Measures for a Mixed Platoon

Abstract: With the precedence of connected automated vehicles (CAVs), car-following control technology is a promising way to enhance traffic safety. Although a variety of research has been conducted to analyze the safety enhancement by CAV technology, the parametric impact on CAV technology has not been systematically explored. Hence, this paper analyzes the parametric impacts on surrogate safety measures (SSMs) for a mixed vehicular platoon via a two-level analysis structure. To construct the active safety evaluation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…( [45]. Deviation in speed, acceleration, and jerk can be attributed as DV [46,47](See Appendix Table A1). Ding et al [48] introduced an average damping ratio (ADR) to show how vehicular oscillations are damped or amplified through a vehicle platoon.…”
Section: ) Individual Ssmsmentioning
confidence: 99%
See 1 more Smart Citation
“…( [45]. Deviation in speed, acceleration, and jerk can be attributed as DV [46,47](See Appendix Table A1). Ding et al [48] introduced an average damping ratio (ADR) to show how vehicular oscillations are damped or amplified through a vehicle platoon.…”
Section: ) Individual Ssmsmentioning
confidence: 99%
“…Conversely, Ye & Yamamoto [47] did not consider any TTC threshold. Instead, the authors showed that the distribution of TTC values for different mixed traffic conditions varied based on the market penetration rate of CAVs.…”
Section: B Study Platforms and Facilities Coveredmentioning
confidence: 99%
“…Transportation networks face many challenges such as high travel times, trafc congestion, crashes, and environmental externalities such as emissions [1][2][3][4]. Congestion is the root of other problems such as increased fuel consumption and increased travel time.…”
Section: Introductionmentioning
confidence: 99%